A Robust Control Strategy for Landing an Unmanned Aerial Vehicle on a Vertically Moving Platform. (15th July 2020) - Aguilar-Ibanez, Carlos; Suarez-Castanon, Miguel S.; Gutierrez-Frias, Octavio; Rubio, Jose de Jesus; Meda-Campana, Jesus A.
Abstract : In this work, we solve the uncertain unmanned aerial vehicle smooth landing problem over a moving platform, assuming that the aircraft position relative to the platform and its acceleration is always measurable. The landing task is carried out by an output-feedback robust controller, together with a repulsive force. The robust controller controls the nominal model, accomplishes the needed tracking trajectory, and counteracts the unknown uncertainties. To assure that the aircraft is always above the platform, we include a repulsive force that only works in a small vicinity of the platform. To estimate the relative aircraft velocity and platform acceleration, we use a supertwisting-based observer, assuring finite-time convergence of these signals. This fact allowed us to design the feedback state stabilizer independently of the observer design (in accordance with the separation principle). We confirmed the effectiveness of our control approach by convincing numerical simulations.